CHARACTERISTICS OF TERMITE ANTI PARTICLE BOARD FROM BINTARO FRUIT FIBER WITH BINTARO FRUIT SEED EXTRACT COATING USING SPRAY COATING METHOD - Delovita Ginting; karnila ila sukma (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2022)
Termites are pests that damage wooden furniture. Termite attacks on wooden furniture are getting higher and wider so that the value of losses due to termite attacks on furniture is increasing from year to year. This research has succeeded in making particle boards from bintaro fruit fibers as fillers and urea formaldehyde resin (UF) as a matrix with a composition of filler mass fractions: the matrix of the particle board to be made is 30:70. The particle board that has been made is then coated using bintaro seed extract and UF resin using the spray coating method. The extract mass fractions of bintaro seeds and UF resins in this study were sample 1 (90:10), sample 2 (80:20), sample 3 (70:30), sample 4 (60:40) and sample 5 (50:50). The physical characterization of particleboard includes density, water absorption and moisture content. The mechanical characterization of particle boards is the bending strength and characterization of particle boards to resistance to termite attacks. The results of this study show that particle boards that have optimum values are sample particle boards 1 with a density value of 0.864 gr / cm³, water absorption of 4.28% which has met SNI 03-2105-2006 and the results of testing the resistance to termites 3.45% have met SNI 01-7207-2006. Because in the manufacture of particle boards are influenced by the structure and physical shape of the raw materials used.